About the Typification of Myriophyllum aquaticum (Haloragaceae) - Tur, Nuncia María (2009)
In 1973, Verdcourt made the combination in Myriophyllum L.: M. aquaticum (Vellozo) Verdcourt based on Enydria aquatica Vellozo in the Haloragaceae. However, significant morphological differences exist between the study of the Vellozo 1825 protologue and the Vellozo 1831 plate of E. aquatica. Therefore, we propose the designation of an epitype to better fix the taxonomic application of the name M. aquaticum (Vellozo) Verdcourt.